University graduates in Peru: sociocultural implications in their research to graduate: University graduates and graduation research - Caramutti de la Piedra, Rosalía del Pilar; Barredo Ibáñez, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In this study we explore the elements that integrate the profiles of university graduates in Peru of the audiovisual communication career and the implications of the sociocultural context in their graduate research. The objective is to identify the profiles of university graduates and the implications of the sociocultural context during the development of the process. With qualitative methodology, the interpretative paradigm model and using the semi-structured interview technique, we identify their perceptions. The conclusions remark that the elements that integrate these profiles have particularities that must be considered when entering the labor market.